Maternal stress and psychological distress preconception: association with offspring atopic eczema at age 12 months. Issue 6 (17th March 2017) - El‐Heis, S.; Crozier, S. R.; Healy, E.; Robinson, S. M.; Harvey, N. C.; Cooper, C.; Inskip, H. M.; Baird, J.; ,; Godfrey, K. M.
Summary: Background: Perinatal maternal stress and low mood have been linked to offspring atopic eczema. Objectives: To examine the relation of maternal stress/mood with atopic eczema in the offspring, focusing particularly on stress/psychological distress preconception. Methods: At recruitment in the UK Southampton Women's Survey, preconception maternal reports of perceived stress in daily living and the effect of stress on health were recorded; in a subsample, psychological distress was assessed (12‐item General Health Questionnaire). Infants were followed up at ages 6 ( n = 2956) and 12 ( n = 2872) months and atopic eczema ascertained (based on UK Working Party Criteria for the Definition of Atopic Dermatitis). At 6 months post‐partum, mothers were asked if they had experienced symptoms of low mood since childbirth and completed the Edinburgh Postnatal Depression Scale. Results: Preconception perceived stress affecting health [OR 1.21 (95% CI 1.08–1.35), P = 0.001] and stress in daily living [OR 1.16 (1.03–1.30), P = 0.014] were associated with an increased risk of offspring atopic eczema at age 12 months but not at 6 months, robust to adjustment for potentially confounding variables. Findings were similar for maternal psychological distress preconception. Low maternal mood between delivery and 6 months post‐partum was associated with an increased risk of infantile atopic eczema at age 12 months, but no significant association between post‐natal mood and atopic eczema was seen after taking account of preconception stress. Conclusion and Clinical Relevance: Our data provide novel evidence linking maternal stress at preconception to atopic eczema risk, supporting a developmental contribution to the aetiology of atopic eczema and pointing to potentially modifiable influences.